Evaluating the sensitivity of dendritic connectivity to fish pass efficiency for the Sesan, Srepok and Sekong tributaries of the Lower Mekong. (August 2018) - Shaad, Kashif; Souter, Nicholas J.; Farrell, Tracy; Vollmer, Derek; Regan, Helen M.
Highlights: Dendritic connectivity index (DCI) is applied on the Sesan, Srepok & Sekong rivers. Considers impact of fish passes in the context of up to 105 current & planned dams. Initially, net connectivity is sensitive to efficiency of individual fish passes. As number of dams in cascade rise, efficient fish passes do not improve DCI scores. Highlights uncertainty of fish pass efficiency and implication on planning. Abstract: Hydropower dam development in the Mekong River Basin is threatening both biodiversity and the output of the world's largest inland fishery. Fragmentation of the river system by dams blocking the free movement of riverine species can have a direct impact on migratory fish species, which constitute a significant portion of the basins wild fishery. Fish passes, which allow fish to bypass dams, are often proposed as potential solutions to these problems. However, there is uncertainty around the effectiveness of fish passes in the species-rich environment of the Lower Mekong, and this has real consequences for the region and its development strategies. As a first step to evaluate the effects of dams in the region, we used the Dendritic Connectivity Index (DCI) to examine the impact on connectivity by providing fish passage on as many as 105 current, under construction and planned dams on the Sesan, Srepok and Sekong tributaries of the Mekong River. Our results indicate that, at the current stage of development, overall connectivity of the river system is sensitive to the efficiency of fish passes – and with highly efficient fish passes, connectivity comparable to a natural network is possible. However, as the number of dams on each tributary increase, even highly efficient fish passes are unable to improve connectivity significantly. While this paper does not explicitly focus on the functioning and limitation of fish passes, this broader analysis clearly establishes that, if constructed, robust monitoring for the newly-designed fish pass on the Lower Sesan II dam would be critical for evaluating and informing future development strategies.